Pengaruh Model Pembelajaran Inquiry Learning untuk Meningkatkan Pemahaman Peserta Didik dalam Mata Pelajaran Informatika di SMPN 3 Bukittinggi - Musthari Annisa Johni nisa; yulifda Elin Yusfita; Eardi Akmal (STKIP Taman Siswa Bima, 2024)
This research is based on informatics learning, students learn informatics at school according to class hours. Learning takes place using conventional learning methods, tends to be centered on the teacher so that students become passive, teachers still use the lecture method in explaining the subject matter so that students become bored with learning and do not understand the subject matter, so that participants do not focus on learning and this affects the students' grades. . The research was conducted with the aim of finding out the effect of implementing the inquiry learning model to improve students' understanding in grade 7 informatics subjects at SMPN 3 Bukittinggi. This research is classroom action research (PTK) with the research subjects being grade 7 students of SMPN 3 Bukittinggi with a total of 28 students. Data collection techniques use tests, observation and documentation. The results of the actions taken from cycle I and cycle II show that the application of the inquiry learning model can improve students' understanding in grade 7 informatics subjects at SMPN 3 Bukittinggi. The results of cycle I showed learning completeness of 64%, or 18 students out of 28 students, and cycle II learning completeness of 86% or 24 students out of 28 students. Thus, the findings from cycle I show that the application of the inquiry learning model can increase students' understanding. ABSTRAK Penelitian ini didasarkan pada pembelajaran informatika, siswa belajar informatika di sekolah sesuai jam pelajaran. Pembelajaran berlangsung dengan metode pembelajaran masih konvensional, cenderung berpusat pada guru sehingga peserta didik mejadi pasif, guru masih menggunakan metode ceramah dalam menjelaskan materi pelajaran sehingga peserta didik menjadi bosan untuk belajar dan tidak memahami materi pelajaran, sehingga peserta tidak fokus belajar dan mempengaruhi nilai peserta didik. Penelitian dilakukan bertujuan untuk mengetahui pengaruh penerapan model pembelajaran inquiry learning untuk meningkatkan pemahaman peserta didik dalam mata pelajaran informatika kelas 7 di SMPN 3 Bukittinggi. Penelitian ini merupakan penelitian tindakan kelas (PTK) dengan subjek penelitian adalah siswa kelas 7 SMPN 3 Bukittinggi dengan jumlah siswa 28 orang. Teknik pengumpulan data menggunakan tes, pengamatan dan dokumentasi. Hasil dari tindakan yang dilakukan dari siklus I dan siklus II menunjukkan bahwa penerapan model pembelajaran inquiry learning dapat meningkatkan pemahaman peserta didik dalam mata pelajaran informatika kelas 7 di SMPN 3 Bukittinggi. Hasil dari siklus I menunjukkan ketuntasan belajar sebesar 64%, atau 18 siswa dari 28 siswa, dan Siklus II ketuntasan belajar sebesar 86% atau 24 siswa dari 28 siswa. Dengan demikian, temuan dari siklus I menunjukkan bahwa penerapan model pembelajaran inquiry learning dapat meningkatkan pemahaman peserta didik